HYPERMOBILITY SYNDROME: CLINICAL MANIFESTATIONS, DIFFERENTIAL DIAGNOSIS, THERAPY APPROACHES - N. A. Shostak; N. G. Pravdyuk (Рациональная фармакотерапия в кардиологии, 2016)
Connective tissue dysplasia (CTD) represents special ontogenetic abnormality which is a complex problem of contemporary medicine. The principles of differential diagnosis of various forms of CTD are considered. A clinical estimation and therapy approaches are discussed with focus on hypermobility syndrome as one of undifferentiated form of CTD.